2004
DOI: 10.2174/0929866043406607
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neuropeptide Processing Enzymes in Endocrine (Prostate) Cancer: EC 3.4.24.15 (EP24.15)

Abstract: The zinc metalloendopeptidase EC3.4.24.15 [EP24.15, thimet oligopeptidase], a neuropeptide processing enzyme, is central to the formation and degradation of many bioactive peptides in the neural proteome, and is highly expressed in normal prostate. EP24.15 actions are increased in androgen-dependent prostate cancer compared to androgen-independent; augmented by androgen treatment, and inhibited by clinical GnRH analogs. The "neural" prostate includes: neuropeptides, cognate receptors and processing enzymes reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Studies using peptide agonists, at least in the case of opioid receptors, have shown that the co-endocytosed agonist is recycled back to the surface or processed in an acidic compartment, depending on the length of agonist treatment (17,53). Relatively few studies have focused on the enzymes that are responsible for post-endocytic peptide agonist degradation, although a number of peptidases have been shown to be capable of hydrolyzing neuroendocrine peptides including opioid peptides (2,45,54,55). Among them, an enzyme named enkephalinase (EC 3.4.24.11), originally thought to be solely responsible for enkephalin degradation, was soon shown to be able to degrade a number of other neuropeptides, and because it exhibited activity at neutral pH it was renamed "neutral endopeptidase" or neprilysin (6,8,56).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using peptide agonists, at least in the case of opioid receptors, have shown that the co-endocytosed agonist is recycled back to the surface or processed in an acidic compartment, depending on the length of agonist treatment (17,53). Relatively few studies have focused on the enzymes that are responsible for post-endocytic peptide agonist degradation, although a number of peptidases have been shown to be capable of hydrolyzing neuroendocrine peptides including opioid peptides (2,45,54,55). Among them, an enzyme named enkephalinase (EC 3.4.24.11), originally thought to be solely responsible for enkephalin degradation, was soon shown to be able to degrade a number of other neuropeptides, and because it exhibited activity at neutral pH it was renamed "neutral endopeptidase" or neprilysin (6,8,56).…”
Section: Discussionmentioning
confidence: 99%
“…Substrate specificity is dependent upon peptide size (< 17 amino acids), without preference for the amino acid sequence [21]. However, a hydrophobic amino acid residue in the P1 and P2 positions along with a bulky hydrophobic residue in the P3′ position increases specificity [22]. The results of studies show that GnRH-(1–5) is biologically active and supports EP24.15’s role as an extracellular processing peptidase and converting enzyme.…”
Section: Control Of the Lh Surgementioning
confidence: 99%
“…This dose has also been widely reported in studies investigating the mechanism of GnRH (or GnRH-like peptides) (Wu et al, 2009. Lastly, alterations in the expression and activity of the GnRH-cleaving enzyme, EP24.15, may promote the synthesis of GnRH-(1e5) as seen in prostate cancer (Swanson et al, 2004); and in our lab using various endometrial cancer cell lines representative of different stages (unpublished data). Furthermore, EP24.15 cleavage of GnRH to GnRH-(1e5) is enhanced 10-fold upon prolyl endopeptidase-mediated removal of the 10th amino acid (Lew et al, 1994).…”
Section: Discussionmentioning
confidence: 54%